Technostress: A Concept Analysis. - Tacy, Joseph W. (Online Journal of Nursing Informatics)
Technology is ubiquitous and can create feelings of frustration, overload, and stress. Technology stress, also called technostress, is an emergent psychological disorder experienced by individuals who use technology. This concept analysis identifies relationships in the contexts of business, education, and nursing. The defining attributes and empirical referents of technostress are analyzed. The relevance of technostress and the acceptance of technology are applied to nursing education.